Laporan Kasus: Burst Abdomen Paska Operasi Laparatomi Kista Ovarium 2 Bulan Lalu (Di RS Luar) - Rezita Rahma Reza Rezita Rahma Reza; Nurul Islamy (MAJORITY, 2021)
Burst abdomen is a postoperative complication that involves tissue damage at the surgical incision site where there is separation due to suture removal that occurs in the surgical wound before the wound healing process is complete. The distended abdomen is part of the complete type of abdominal dehiscence wound. The risk factors for burst abdomen can be classified into three groups, namely pre-operative risk factors, intra-operative risk factors, and post-operative risk factors. This study is a case report at RSUD Abdul Moeloek Bandar Lampung. It is reported that a 48-year-old woman came with complaints of abdominal pain due to open stitches since 1 week ago, after undergoing laparotomy for ovarian cysts 2 months ago at an external hospital. Abdominal pain occurs around the open surgical wound about 8 cm x 1cm x 4cm with pus and blood. The risk factors obtained in the patient were pre-operative risk factors in the form of a history of diabetes mellitus and anemia. The patient was treated in the form of a re-closure operation with the Smead Jones Suture suture technique.